2019
DOI: 10.1038/s41419-019-1415-6
|View full text |Cite
|
Sign up to set email alerts
|

PBK, targeted by EVI1, promotes metastasis and confers cisplatin resistance through inducing autophagy in high-grade serous ovarian carcinoma

Abstract: High-grade serous ovarian carcinoma (HGSOC) is the most lethal type of gynecologic malignancy. Chemoresistance is the main reason for the poor prognosis of HGSOC. PDZ-binding kinase (PBK) promotes the malignant progression of various carcinomas. However, the roles and clinical significance of PBK in HGSOC remain unclear. Here, we reported that PBK was overexpressed in HGSOC tissues and cell lines. High PBK expression was associated with a poor prognosis, metastasis, and cisplatin resistance of HGSOC. Overexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 57 publications
3
41
0
Order By: Relevance
“…Since we previously reported that the autophagic pathway was altered in response to acute iron overload conditions in gynecological cells 30 and that EVI1 expression may regulate the expression of PDZ-binding kinase which leads to increased autophagy to confer chemoresistance 58 , we next investigated whether chronic iron exposure may also alter the autophagic pathway. We identified a subtle reduction in both LC3B-I and LC3B-II (the nonconjugated and conjugated forms, respectively) protein without a clear notable change in p62/sequestosome protein (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since we previously reported that the autophagic pathway was altered in response to acute iron overload conditions in gynecological cells 30 and that EVI1 expression may regulate the expression of PDZ-binding kinase which leads to increased autophagy to confer chemoresistance 58 , we next investigated whether chronic iron exposure may also alter the autophagic pathway. We identified a subtle reduction in both LC3B-I and LC3B-II (the nonconjugated and conjugated forms, respectively) protein without a clear notable change in p62/sequestosome protein (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, some studies found that autophagy inhibits the malignant biological behavior of tumors [15, 16]. PBK promotes the metastasis of serous ovarian carcinoma and confers cisplatin resistance [17]. OGT was downregulated in ovarian cancer, which in turn, promotes cisplatin resistance by inducing autophagy [18].…”
Section: Discussionmentioning
confidence: 99%
“…This might explain why a high EVI1 expression indicates a poor survival in several tumor types and not in HNSCC. For example, in colon and ovarian cancer, EVI1 is associated with a higher metastasis rate [31,33]. A formation of several subgroups by p16 status and place of origin might show that in one or the other subgroup, a high EVI1 expression is associated with a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%